The Influence of Leverage, Financial Performance, and Capital Structure on Firm Value: An Islamic Perspective with Managerial Ownership as a Moderating Variable - Utami, Galuh Mega; Waskito, Jaka; Utami, Yuni (UNISSULA, 2025)
The objective of this research is to assess the extent to which leverage, financial performance, and capital structure affect firm value, and to evaluate whether managerial ownership moderates these relationships with empirical evidence sourced from energy companies registered on the IDX for the 2021–2024. The analysis uses 88 samples from a population of 83 companies, selected using purposive sampling. This study employs quantitative data from published financial statements on the IDX for 2021–2024. Data processing employed multiple linear regression and MRA, utilizing SPSS as the analytical tool. The study finds that leverage and financial performance significantly enhance firm value. Meanwhile, capital structure does not significantly enhance firm value. Furthermore, managerial ownership moderates the relationship between leverage and firm value by strengthening the effect, and moderates the relationship between capital structure and firm value by weakening the effect. However, managerial ownership does not significantly influence the interplay between financial performance and firm value.